2015
DOI: 10.1089/zeb.2014.1062
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin O-Acyl Transferase in Zebrafish Is an Evolutionarily Conserved Peptide Upregulated During Calorie Restriction

Abstract: Ghrelin is a multifunctional orexigenic hormone with a unique acyl modification enabled by ghrelin O-acyl transferase (GOAT). Ghrelin is well-characterized in nonmammals, and GOAT sequences of several fishes are available in the GenBank. However, endogenous GOAT in non-mammals remains poorly understood. In this research, GOAT sequence comparison, tissue-specific GOAT expression, and its regulation by nutrient status and exogenous ghrelin were studied. It was found that the bioactive core of zebrafish GOAT amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 58 publications
4
15
1
Order By: Relevance
“…Food deprivation is known to play a significant role in altering neuroendocrine factors that play critical role in reproduction and energy intake in several species 13 24 . In goldfish, fasting for 7 or 28 days did not result in any significant changes in body weight and this result is in agreement with previous reports in goldfish 25 26 27 . NUCB1 expression in gut was significantly lower when fish were food deprived for one week 13 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Food deprivation is known to play a significant role in altering neuroendocrine factors that play critical role in reproduction and energy intake in several species 13 24 . In goldfish, fasting for 7 or 28 days did not result in any significant changes in body weight and this result is in agreement with previous reports in goldfish 25 26 27 . NUCB1 expression in gut was significantly lower when fish were food deprived for one week 13 .…”
Section: Discussionsupporting
confidence: 93%
“…For IHC studies conducted as described in detail earlier1626, pituitary, ovary, J-loop and testis were collected from goldfish. The antibodies used were: rabbit polyclonal anti- mouse nucleobindin-1 (Pacific immunology, Ramona, CA) for NUCB1, mouse monoclonal anti-growth hormone (Catalog # CLX 130AP, 1:500, Cedarlane, USA) for growth hormone in pituitary, mouse monoclonal anti-ghrelin hormone (Catalog # ab57222, 1:500, Abcam, Massachusetts) for ghrelin in J-Loop11, mouse monoclonal anti-SOX9 hormone (Catalog # ab76997, 1:500, Abcam, Massachusetts) for SOX9 in testis2033, goat monoclonal anti-FOXL2 hormone (Catalog # PA5-18175, 1:500, Waltham, MA ) for FOXL22033 staining in ovary respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that GOAT might be restrictedly distributed within the mammalian brain and then, its transcripts are detected when discrete locations are analysed separately. In fish, the only study available points out that GOAT seems to be more widely distributed within the brain, as important levels of goat mRNA expression are observed in the whole brain of zebrafish using RT‐qPCR (Hatef et al, ). Results from the present study show a broad expression of goat in the goldfish brain by RT‐qPCR, in agreement with zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Although in lower levels, mRNAs encoding this enzyme were also detected in hypothalamus, pituitary, taste cells, heart, kidney, ovary, placenta, adipose tissue, muscle, serum and chondrocytes of mammals (Gonz alez et al, 2008;G omez et al, 2009;Sakata et al, 2009;Gahete et al, 2010;O'Brien et al, 2010;Shin et al, 2010;Rucinski et al, 2012). In fish, a recent study has shown that GOAT is mainly expressed in gut, gonads and brain of zebrafish (Hatef et al, 2015). Given that the gastrointestinal tract is the main tissue expressing GOAT, further studies using imaging techniques have demonstrated that GOAT is specifically located in the gastric mucosal cells (Sakata et al, 2009;Stengel et al, 2010;Hatef et al, 2015) where it colocalizes with ghrelin in both mammals (Sakata et al, 2009;Stengel et al, 2010) and fish (Hatef et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…tive cells in the gonads will assist us in predicting possible reproductive regulatory roles of PNX in zebrafish. Immunohistochemical studies (IHC) were conducted using methods described earlier 35 . The details of antibodies used in our research are rabbit anti PNX-14 primary antibody (Phoenix Pharmaceuticals, Burlingame, CA, United States, 1:1000 dilution) and rabbit anti-SREB3 antibody -N-terminal (Abcam, Cambridge, UK, 1:500 dilution).…”
Section: Immunohistochemial and Immunocytochemical Localization Of Pnmentioning
confidence: 99%